2017
DOI: 10.3906/biy-1612-17
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of etoposide to osteosarcoma cells using poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) nanoparticles

Abstract: Folic acid (FA)-functionalized poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) nanoparticles were prepared to enhance the delivery efficiency of the anticancer drug etoposide for the clinical treatment of osteosarcoma. PHBV nanoparticles were synthesized by emulsification/solvent evaporation technique and obtained in the size range of 200-250 nm and zeta potential range of -21 and -27 mV. Encapsulation efficiency and in vitro drug release were studied. The cytotoxic, apoptotic, and necrotic effects of PHBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The prepared microspheres were centrifuged at 3000 rpm for 5 min and the drug concentration in the supernatant was determined by a UV–visible spectrophotometer (Nanodrop1000, Thermo USA) at a wavelength of maximum ( λ max ) 263 nm. Drug EE of microspheres was calculated by the following formula [15]:E E )(% = normalTotal thinmathspacenormalamount thinmathspacenormalof thinmathspacenormalSorafenib normalAmount thinmathspacenormalof thinmathspacenormalfree thinmathspacenormalSorafenib thickmathspace normalTotal thinmathspacenormalamount thinmathspacenormalof thinmathspacenormalSorafenib × 100. The release profile of sorafenib from microspheres was examined in PBS solution (pH 7.4) [16]. In brief, 0.25 mg/ml sorafenib was loaded into the prepared microspheres and microsphere‐sorafenib suspension was centrifuged at 3000 rpm for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The prepared microspheres were centrifuged at 3000 rpm for 5 min and the drug concentration in the supernatant was determined by a UV–visible spectrophotometer (Nanodrop1000, Thermo USA) at a wavelength of maximum ( λ max ) 263 nm. Drug EE of microspheres was calculated by the following formula [15]:E E )(% = normalTotal thinmathspacenormalamount thinmathspacenormalof thinmathspacenormalSorafenib normalAmount thinmathspacenormalof thinmathspacenormalfree thinmathspacenormalSorafenib thickmathspace normalTotal thinmathspacenormalamount thinmathspacenormalof thinmathspacenormalSorafenib × 100. The release profile of sorafenib from microspheres was examined in PBS solution (pH 7.4) [16]. In brief, 0.25 mg/ml sorafenib was loaded into the prepared microspheres and microsphere‐sorafenib suspension was centrifuged at 3000 rpm for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Folate, a targeting ligand, was incorporated to facilitate the tumor uptake of nanoparticles. [15] The authors demonstrated the increase in direct antitumor activity of zoledronate by 80 to 85% in vivo, compared to free drug, which could be explained by the improved tumor uptake and the prolonged drug release kinetics. [47] Similarly, an intelligent nano drug delivery system composed of functional graphene oxide conjugated with folic acid, polyethylene glycol, and photosensitizer indocyanine green was developed for the delivery of MutT homolog 1 inhibitor and doxorubicin.…”
Section: Osteoarthritismentioning
confidence: 99%
“…[44] Advances in nanotechnology have led to the development of multifunctional nanomaterials as diagnostic and therapeutic agents which can target bone tumor and deliver drugs and genes selectively to the targeted cells. [15,45] Targeted delivery and controlled release of chemotherapeutic agents by nanocarriers prevent rapid clearance of the drug, prolong blood circulation time, enhance intra-tumoral accumulation, thereby, improving therapeutic efficacy and minimizing side effects. [45] A cisplatin-crosslinked, doxorubicin-loaded hyaluronic acid nanogel was reported for the effective treatment of osteosarcoma.…”
Section: Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, HV content of PHBV was considered 2% and 8% (33)(34)(35)(36)(37), PEG/PHBV varied in the range of 15-25% (38)(39)(40)(41)(42), and two molecular weights of PEG (MW 3350 and 6000) were used for the study.…”
Section: Preparation and Optimization Of Bz-phbv Implantsmentioning
confidence: 99%